Optimisation design of an energy management strategy for hybrid vehicles. (30th August 2006) - Zhu, Yuan; Chen, Yaobin; Wu, Zhihong; Wang, Aihua
This paper presents an innovative method to analyse and design an optimal energy management strategy for a power-split power train hybrid vehicle. A hybrid dynamical system theory is introduced to formulate the problem of hybrid vehicle control system design that incorporates both continuous and discrete dynamics. The sequential quadratic programming method is proposed to optimise power distribution. The dynamic programming method is employed to determine the vehicle operating mode transitions with optimal fuel efficiency and satisfactory drivability. An expert rule-based system and a fuzzy system are developed to implement the optimal strategies using the statistical method based on numerical solutions. The simulation results illustrate the effectiveness and applicability of the proposed design method.